Investment Funds and Financial Stability : Policy Considerations - Garcia Pascual, Antonio (Departmental Papers; Departmental Paper, 2021)
The paper's analysis underscores the importance of the ongoing Financial Stability Board-led process of identifying policy options, involving national authorities and the International Organization of Securities Commissions and other standard setters. In this context, the global nature of the investment fund business and fungibility of financial flows makes it vital to ensure consistency of global policy choices that can secure financial stability by precluding regulatory arbitrage.